Ancient DNA and the rewriting of human history: be sparing with Occam's razor. Issue 1 (December 2016) - Haber, Marc; Mezzavilla, Massimo; Xue, Yali; Tyler-Smith, Chris
Abstract Ancient DNA research is revealing a human history far more complex than that inferred from parsimonious models based on modern DNA. Here, we review some of the key events in the peopling of the world in the light of the findings of work on ancient DNA.